Financial reporting of goodwill impairment of Malaysian listed companies - Ahmad, Maizatul Akhmam (2011)
The introduction of FRS 136 Impairment of Assets in Malaysia presents an opportunity for this study to examine the association between the firms’ compliance on goodwill impairment disclosure and firm characteristics. Drawing on agency theory, this study explores whether association exist between mandated disclosure for goodwill impairment test with company characteristics. In particular, the association tested between goodwill impairment disclosure and company characteristics (namely profitability, ownership, audit committee financial expertise, audit quality, size and leverage. This study measures the mandated compliance on goodwill impairment disclosure based on six categories of information required under paragraph 134 of FRS 136 Impairment of Asset. A total disclosure score has been developed to measure the extent of goodwill impairment disclosure of each sample firm. Final sample of 116 firms listed on the Main Board of Bursa Malaysia with reported goodwill as an element of their asset in the Balance Sheet as at 31 December 2007 are used in this study. The relationship between goodwill impairment disclosure and the firm characteristics is analyzed using regression analysis. The results indicate that the companies in general do not fully disclose the requirement of paragraph 134 of FRS 136 as prescribed. On average, only 65.5% of the items required by the respective section under FRS 136 are disclosed by the companies, indicating that almost half of the required disclosures are not met. In addition, the study finds no significant result between ownership status of the company, i.e., whether a company is Government Linked Company (GLC) or Non Government Linked Company (NGLC) and goodwill impairment disclosure. There is no significant result obtained in the presence of audit committee member with financial expertise and audit quality as Big 4 and non Big 4. However, the study finds that profitability and firm size are significantly associated with goodwill impairment disclosure. Further, the study also finds the quality of goodwill impairment disclosure among Malaysian firm is still low suggesting that compliance with goodwill impairment disclosure is problematic. The findings hope to provide some useful insights to users, preparers and standard setters into goodwill impairment disclosure in the annual reports.